Managing cultural tourism in a post-conflict region: the Kurdistan Federal Region of Iraq - Braim, Kadhim Magdid (2018)
During any period marked by conflict, potential investors (domestic and foreign) are reluctant to invest in the tourism sector of a country or region, owing to weak investor protection and the general climate of instability, in parallel with the lack of comprehensive planning for the tourism industry. Moreover, after a period of conflict, major challenges have to be faced in rebuilding the social, cultural, educational, service and economic infrastructure. Thus, the tourism industry in conflict and post-conflict areas often suffers a number of challenges, in the form of poor infrastructure, low investment and a lack of proper tourism management planning, or, poor implementation. In the case of the Kurdistan Federal Region of Iraq (KFR), conflict caused major challenges to heritage protection and consequently to the development of cultural tourism. The region was subject to ethnic conflict between the Iraqi government and Kurdish opposition, in particular the armed conflict in 1961 to 2003. There was lack investment in transport infrastructure. The absence of essential facilities such as motorways, rail networks and airports severely restricted the development of a tourism industry from 1991 (the year in which Kurdish autonomy in the region was achieved) to 2005 (when the KFR was officially recognised in Iraq's Constitution of 2005) and continued until 2006. Thereafter, the tourism industry recorded an increase of approximately 700% from 2007 to 2013, after the building of two international airports and thousands of miles of motorways in the KFR. However, so far, in the KFR, no consideration has been given to the conservation of cultural heritage, either as a legacy to the nation or in terms of its potential use to develop tourism. This underdevelopment is attributable to a number of problems, but notably the conflict, which led to the lack of an integrated tourism policy, lack of knowledge on how to protect heritage assets, poor infrastructure and low investment. The preservation of heritage assets has been discussed in the literature, but mostly the focus is on preservation of resources in the context of sustainable tourism (often in the context of over-utilization), and there is a lack of studies undertaken to investigate how post-conflict issues affect the protection of heritage assets, that is, what the potential challenges are to the conservation of heritage assets in post-conflict countries, and how these challenges impact on the future potential for cultural tourism development. This thesis investigates how post-conflict issues affect heritage protection and cultural tourism, in terms of both planning and management, by exploring heritage protection and cultural tourism in the KFR as an example of both a post-conflict area and a new autonomous region. It suggests solutions and makes recommendations for the development of successful, competitive and sustainable cultural heritage tourism in the KFR. The results show that the KFR is rich in cultural resources, but currently not enough governmental consideration is given to cultural heritage conservation. The managerial issues caused by lack of legislation and poor government administration, in parallel with some other challenges, notably a lack of funding, are the core barriers to investment in heritage protection in the KFR, and consequently creating major problems to the development of cultural tourism. Other issues include: a lack of investment and poor implementation, a negative destination image and marketing difficulties. The findings will help decision makers to develop a strategy for cultural protection and to establish a proper cultural tourism policy in the KFR through recommendations to government. The findings will also be of interest to other post-conflict nations and regions. The thesis reports data from a series of focus groups and in-depth interviews conducted in 2015 and 2017.